Femmes réfugiées dans les centres de rétention administrative en Grande-Bretagne - Catherine Puzzo (Anglophonia)
Women refugees constitute a particularly vulnerable population who, for different reasons, are often detained in immigration removal centres in the UK. Their precarious legal status is worsened by very difficult communication with administrative and political authorities. In the specific context of their detention the voice of these women needs to be listened to and it is the aim of this paper to look at the role and performance of various agencies and associations that talk about and/or talk in the name of these women. The position of institutional bodies such as Her Majesty’s Inspectorate of Prisons and the Women’s National Commission is successively examined to determine the extent of their contribution to bringing these women’s voices to policymakers and ministers. This paper also examines the significant role of associations in charge of defending and promoting women refugees’ rights. In particular it seeks to assess whether the lobbying role of these cause groups has had an impact upon the definition of substantive policy issues regarding women refugees and upon the identification of significant shortcomings across the sector.